PLATELET FUNCTION TEST FOR THE ASSESSMENT OF THROMBOSIS AND BLEEDING RISK IN CHD PATIENTS TAKING ANTIPLATELET MEDICATIONS - A. L. Komarov; E. P. Panchenko (Российский кардиологический журнал)
The review concerns on the testing of platelet function in Chd patients receiving antiplatelet medications.  the results are shown of the main large-scale studies demonstrating the relationship of the residual platelet activity level with the development of ishemic and hemorrhagic complications. the analysis is done of the causes of insufficient suppressing of platelet function as the response to clopidogrel. the guidelines of major international expert organizations are discussed on problem of sensitivity to aggregants testing and possible modification of antiplatelet treatment.